Ecological design for the propagation of Sycanus dichotomus in insectariums for sustainable oil palm pest management - SEPTA PRIMANANDA; SAMHARINTO SOEDIJO; AKHMAD GAZALI; NOOR AIDAWATI; CINDY DIAH AYU FITRIANA; SUKARMAN SUKARMAN; AGUS EKO PRASETYO; TJUT AHMAD PERDANA ROZZIANSHA (Society for Indonesian Biodiversity, 2025)
Abstract. Primananda S, Soedijo S, Gazali A, Aidawati N, Fitriana CDA, Sukarman, Prasetyo AE, Rozziansha TAP. 2025. Ecological design for the propagation of Sycanus dichotomus in insectariums for sustainable oil palm pest management. Biodiversitas 26: 617-627. The oil palm industry plays a substantial role in national and global economies, and sustainable agricultural practices are critical to its longevity including aspects related to pest management. This study aimed to identify effective methods for propagating the predatory insect Sycanus dichotomus as part of integrated pest management in oil palm plantations. The primary focus is on ecological design within the insectarium, selecting appropriate refugia plants, and determining the sex ratio to support an efficient predator population. The study was conducted at an oil palm plantation in Central Kalimantan, Indonesia, which serves as a natural ecosystem for S. dichotomus. A multifactorial experimental design was employed, combining variables such as insectarium type manifested as paranet density, adults sex ratio, and refugia plant type. The most optimal results for enhancing the productivity of the predator S. dichotomus were achieved using an insectarium with 100% sunlight intensity, a sex ratio of males to females of 2:4, and Cassia cobanensis as the host plant. The maturation rate from eggs to nymphs increased in an insectarium with 25% sunlight intensity and Antigonon leptopus as the host plant, resulting in high fertility and the presence of 1st, 3rd, and 5th instar nymphs. The interaction between egg groups and the total eggs was highly correlated (80%), and the development of instar 1 and instar 3 showed a fair correlation at 60%, indicating key relationships that support the predator's growth and reproduction under these conditions. Additionally, the study demonstrated that balancing sunlight exposure and selecting appropriate host plants significantly affect the development and reproductive success of S. dichotomus. This research highlights the importance of microclimatic conditions in the insectarium, refugia plants, and sex ratio as crucial factors for rearing S. dichotomus. It provides important insights for the propagation of predator techniques to support the sustainable oil palm industry. These findings underscore the importance of an integrated approach to pest management, ensuring long-term sustainability and economic viability in oil palm cultivation.